Efficiency application of running exercises with skandinavian sticks in the complex strength training of young biathletes - Sagiev, T.; Gibadullin, I. (BIO Web of Conferences, 2020)
The authors of the article based on the systematization of data from scientific and methodological literature and analysis of training young biathletes practice developed a block-modular technology of complex strength training in the snow-free period, and also modified scandinavsky walking as a type of active activity to running exercises with Scandinavian sticks in order to develop strength endurance of the shoulder girdle muscles. Based on the conducted pedagogical experiment, the authors came to the conclusion that it is advisable to reduce cross-country training by 30-40% in the snow-free period due to the use of running exercises with Scandinavian sticks. The combination of block-modular complex strength training with Scandinavian sticks exercises allows us to most effectively increase the indicators of the shoulder girdle muscles power endurance and functional readiness of biathletes aged 13-16 years.